The human right to democracy (2014)
Starting from the conception of the new global conditions of the international system, this paper aims to develop the human right to democracy and the involvement of the recognition of this in the political, the author determines that democracy is still a legal and constitutional limits to arbitrary exercise of political power. This paper develops starting from the concept of globalization, determining here that democracy is one of the new global conditions of the international system. Also the recognition and universal rights fundamental key in the development of this work and the different conceptions of democracy and the exercise of this, leading eventually to an interesting conclusion that results from an approach around Democracy considered a human right and as an overall condition of the international system, with a key role in its development.